2022
DOI: 10.1055/a-1783-8154
|View full text |Cite|
|
Sign up to set email alerts
|

Individualized treatment of differentiated thyroid cancer: The value of surgery in combination with radioiodine imaging and therapy – A German position paper from Surgery and Nuclear Medicine

Abstract: A consensus statement about indications for post-surgical radioiodine therapy (RIT) in differentiated thyroid cancer patients (DTC) was recently published by the European Thyroid Association (ETA) 1. This publication discusses indications for RIT on the basis of an individual risk assessment. Many of the conclusions of this consensus statement are well founded and accepted across the disciplines involved. However, especially from the perspective of nuclear medicine, as the discipline responsible for indicating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…The fact that even patients with a low risk can show persistent disease, even if they are few, should be kept in mind. This is an important aspect to consider in everyday clinical practice and should be carefully taken into account, especially with regard to the currently discussed indication for radioiodine therapy [ 15 , 16 ]. A recent German position paper by nuclear medicine physicians and endocrine surgeons, written by Schmidt et al, summarizes areas of disagreement based on a literature review in comparison with the ATA [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The fact that even patients with a low risk can show persistent disease, even if they are few, should be kept in mind. This is an important aspect to consider in everyday clinical practice and should be carefully taken into account, especially with regard to the currently discussed indication for radioiodine therapy [ 15 , 16 ]. A recent German position paper by nuclear medicine physicians and endocrine surgeons, written by Schmidt et al, summarizes areas of disagreement based on a literature review in comparison with the ATA [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is an important aspect to consider in everyday clinical practice and should be carefully taken into account, especially with regard to the currently discussed indication for radioiodine therapy [ 15 , 16 ]. A recent German position paper by nuclear medicine physicians and endocrine surgeons, written by Schmidt et al, summarizes areas of disagreement based on a literature review in comparison with the ATA [ 15 ]. The ATA and the ETA are cautious about RAI in low-risk patients and see the indication for it only in individual exceptional cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The decision to treat with RAI following thyroidectomy and the level of activity to administer should be based on the riskbenefit ratio. The benefit of RAI therapy, especially for low-risk differentiated thyroid cancer (DTC) patients, remains controversial (3)(4)(5). Leboulleux et al showed in a prospective, randomised, phase 3 trial (ESTIMABL2) of patients with low-risk DTC [T1(m) N0 M0] that surveillance is non-inferior to RAI therapy for event-free survival at 3 years (6).…”
Section: Introductionmentioning
confidence: 99%
“…[2]. In addition, not long ago, a German position paper from surgery and nuclear medicine was published in reaction to the ETA Consensus Statement with a very different perspective, similar to the newly published SNMMI/EANM guideline [3]. Overall, despite the use of the widely accepted riskadapted therapy, its interpretation and relative approaches to DTC management, and in particular to the clinical use of radioactive iodine, still differ significantly in European countries [4].…”
mentioning
confidence: 99%